Development of energy converters in discrete ion-plasmodynamic installations with electronic control - A. S. Chipura; M. V. Dolgopolov; D. E. Ovchinnikov; A. V. Radenko; V. V. Radenko (Вестник Самарского университета: Естественнонаучная серия)
Methods for generating electronically controlled ion and plasma fluxes in magnetic fields have been developed for neutron generator, plasma electric generator, and klistron-based generator. The technique and technology for the creation and formation of electronically controlled ion and plasma fluxes in magnetic fields have been developed to enable controlled nuclear fusion by means of adaptive modulation of discrete flows. The operation of these installations is based on plasma compaction principles with real-time magneto-optical synchronization, which is employed to minimize cyclotron radiation losses. This work provides a comprehensive methodology for experimental validation, focusing on high-energy photon detection (6–17 MeV range) and alpha particle shielding via 50 μm titanium foil, essential for industrialscale plasma generator testing. Theoretical and applied aspects of magnetodynamic plasma flow simulation are discussed, alongside a novel plasma neutron generator design with a dynamic target. The proposed electronically controlled plasma energy converter achieves a thermal output power of 8–25 kW and electrical power of 4–12 kW, surpassing conventional D-T systems in energy conversion efficiency (50 %). A neutron generator with a plasma target impulse flux up to 1010 s−1 is proposed, highlighting advancements over conventional D-T systems. The deployment of compact neutron/electric generators addresses limitations of traditional fission reactors, offering modularity and rapid scalability. Recent innovations include pulsed D-T generators and hybrid laser-plasma systems, yet energy conversion efficiency remains suboptimal (30 %). Our work introduces an electronically controlled plasma generator utilizing lithium hydride evaporation and quadrupole magnetic discretization (Patent RU 2757666), achieving 50 % efficiency via adaptive ion flux synchronization. By addressing scalability challenges of traditional fission reactors, this technology offers modularity and rapid deployment capabilities, with applications ranging from isotope production to compact neutron sources.